Scope and mechanistic aspect of nickel-catalyzed alkenylation of benzothiazoles and related azoles with styryl bromides - Patel, Ulhas N.; Jagtap, Rahul A.; Punji, Benudhar (Organometallics, 2019)
Alkenylation of benzothiazoles and related azoles with alkenyl bromides is achieved employing the well-defined and air-stable nickel complexes, (bpy)NiBr2 and [Ni(bpy)(3)] [NiBr4], as catalysts. Numerous electronically distinct alkenyl bromides efficiently coupled with substituted benzothiazoles, oxazoles, and benzimidazoles under the catalytic conditions to afford 2-alkenylated azoles. An extensive mechanistic study of the alkenylation of benzothiazole using (bpy)NiBr2 highlights a single-electron transfer process for the reaction involving the two-step one-electron oxidative addition of alkenyl bromide. The substrate benzothiazole plays a significant and diverse role in the reaction, and C-H bond cleavage is reversible in nature. Detailed kinetic analysis and control reactivity studies are indicative of a Ni(I)/Ni(III) pathway for the alkenylation comprising the rate-influencing reductive elimination step.